Legal Vacuum in the Regulation of Unregistered New Narcotics Types and the Absence of Legislation - Iwansyah Iwansyah; Zudan Arief Fakrulloh (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The study aims to analyze the legal gaps related to the regulation of new types of narcotics that have not been registered. This research employs a normative legal research method, which focuses on analyzing the existing legal provisions as stated in the relevant laws and regulations. The purpose is to examine how these legal frameworks address the emergence of new types of narcotics, especially those not yet registered in Indonesia. With the rapid development of synthetic drugs and other new narcotic substances, existing laws often struggle to keep up with emerging challenges. The normative legal research approach is particularly suitable for this study because it enables a critical examination of how the current legal system responds to these developments and whether it provides adequate legal tools to address such issues. Through this approach, the study will explore the gaps in existing positive law and assess how these legal voids impact the implementation of anti-drug policies and law enforcement in Indonesia. One key issue identified is the inability of current narcotics laws to effectively regulate or prevent the circulation of new, unregistered substances. This lack of legal recognition creates challenges for law enforcement agencies in controlling the distribution and use of such narcotics. Furthermore, the study will analyze the implications of these legal gaps on public health, law enforcement practices, and the overall effectiveness of anti-drug efforts in Indonesia. By identifying the shortcomings in the regulation of new narcotics types, the research aims to provide recommendations for improving legal frameworks and ensuring that laws evolve in tandem with emerging drug trends. Ultimately, this study contributes to enhancing the legal response to narcotic-related issues and supports the development of more effective drug control policies in Indonesia.